Severe Clinical Insomnia Management with Ayurvedic Protocol - A Case Report (International Journal of Ayurveda and Pharma Research, 2024)
Insomnia is characterized by inability to sleep or lack of sleep. Severe clinical insomnia is a highly prevalent health concern faced by a wide majority of people across the globe due to the rise in stressful external environments. Often such cases require long term use of sedative hypnotics or tranquilizers which are habit forming. Ayurveda identifies insomnia as Nidranasa and is a disease which is caused predominantly by Vata Pitta increase and a dip in Kapha levels. Ayurvedic treatment protocol involves internal medication and topical procedures like Shirodhara and Abhyanga. This case report is intended to throw light to a positive outcome of Ayurvedic treatment protocol in severe clinical insomnia. A 34-year-old male presented with symptoms of severe clinical insomnia assessed by Insomnia Severity Index (ISI) associated with obesity and had a history of consuming hypnotics. The treatment protocol included Dhanyamladhara, Udvartana, Takradhara, Abhyanga and Shirodhara along with disease specific internal medicines. The ISI score before treatment of 26 came down to 1 after treatment and was maintained during 3 months follow up. This displays the complete remission of the disease without the use of habit-forming internal medication.